Analisis Miskonsepsi Buku Biologi Kurikulum 2013 Kelas X Pada Materi Ekosistem - Syarifah Widya Ulfa; Fany Erlangga Saragih; Yulianti Sinurat; Putri Rizq Achyari; Raini Dahriana Pulungan; Muhammad Fazil Mawla Lubis (Journal Innovation In Education, 2024)
This research analyzes misconceptions in the 2013 Biology curriculum book for class X, especially regarding ecosystem material. Using qualitative descriptive methods, this research identifies parts of the book that have the potential to cause misconceptions and involves interviews and questionnaires with students and teachers. The results show that less than 10% of concepts experience misconceptions, with the highest level of misconceptions in the concepts of food chains and energy flow. Most misconceptions are caused by students' lack of understanding of teacher explanations that are difficult to understand. Students tend to look for references on the internet to clarify material, but this also has the potential to increase misconceptions if the source is not clear. Lecture-based learning methods and the use of PowerPoint media without in-depth explanations also contribute to misconceptions. This research emphasizes the importance of meaningful and participatory learning to reduce student misconceptions.